2009
DOI: 10.1098/rspb.2009.0851
|View full text |Cite
|
Sign up to set email alerts
|

Express your personality or go along with the group: what determines the behaviour of shoaling perch?

Abstract: Behavioural syndromes, defined as correlated behaviours in different contexts, have been studied across species and taxa including humans as part of a personality concept. While most studies have focused on solitary individuals, less is known on how shoaling fish compromise between own personality and group behaviour. Risk-taking behaviour in 1-year-old perch (Perca fluviatilis) was observed to compare individual behaviour when in a group and when alone. An experimental design gave the fish the choice between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 41 publications
(60 reference statements)
6
94
3
1
Order By: Relevance
“…Shoaling tendency in fish has been shown to be both heritable (Dochtermann, Schwab, & Sih, 2015; Wright, Rimmer, Pritchard, Krause, & Butlin, 2003) and repeatable (Magnhagen & Bunnefeld, 2009; Ward et al., 2004). Therefore, if more social fish tend to be found in larger groups in the wild, then it is possible that sociability as a trait could be under selection in trap fisheries.…”
Section: Discussionmentioning
confidence: 99%
“…Shoaling tendency in fish has been shown to be both heritable (Dochtermann, Schwab, & Sih, 2015; Wright, Rimmer, Pritchard, Krause, & Butlin, 2003) and repeatable (Magnhagen & Bunnefeld, 2009; Ward et al., 2004). Therefore, if more social fish tend to be found in larger groups in the wild, then it is possible that sociability as a trait could be under selection in trap fisheries.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also report that the maintenance of these traits depends on both the level of the trait and state dependencies. In perch (Perca fluviatilis), for example, traits such as time spent in open habitat are consistently expressed between asocial and social contexts (groups of four fish); however, bolder individuals changed their behaviour less between contexts [46]. Similarly, three-spined sticklebacks (Gasterosteus aculeatus) maintain their behavioural traits in a pair, where the bolder individual of the pair will initiate more foraging trips, while a shyer individual will follow [11,47].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has recently Personality and the spread of invasion J. Cote et al 1577 been shown that the expression of personality might depend on group composition and even that the personality of others matters in the formation of a group (Harcourt et al 2009;Magnhagen & Bunnefeld 2009) and the behaviours of conspecifics also matter in dispersal decisions. More experiments are needed to test how individual social behaviour interacts with average social behaviour in the population.…”
Section: Discussion (A) Individual Consistency and Behavioural Syndromesmentioning
confidence: 99%